2011
DOI: 10.1158/1535-7163.mct-10-1044
|View full text |Cite
|
Sign up to set email alerts
|

Potent Activity of Ponatinib (AP24534) in Models of FLT3-Driven Acute Myeloid Leukemia and Other Hematologic Malignancies

Abstract: Ponatinib (AP24534) is a novel multitargeted kinase inhibitor that potently inhibits native and mutant BCR-ABL at clinically achievable drug levels. Ponatinib also has in vitro inhibitory activity against a discrete set of kinases implicated in the pathogenesis of other hematologic malignancies, including FLT3, KIT, fibroblast growth factor receptor 1 (FGFR1), and platelet derived growth factor receptor α (PDGFRα). Here, using leukemic cell lines containing activated forms of each of these receptors, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 26 publications
7
89
0
1
Order By: Relevance
“…Cell viability and growth were assessed using the CellTiter 96 Aqueous One Solution Cell Proliferation Assay (Promega; ref. 39).…”
Section: Ba/f3 Tel-fgfr Cell Viability Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…Cell viability and growth were assessed using the CellTiter 96 Aqueous One Solution Cell Proliferation Assay (Promega; ref. 39).…”
Section: Ba/f3 Tel-fgfr Cell Viability Assaymentioning
confidence: 99%
“…Cellular lysates (50 mg) were resolved by electrophoresis and membranes immunoblotted with antibodies against phospho and total proteins (39). IC 50 values were calculated by plotting percentage of phospho-protein normalized to total protein, or glyceraldehyde-3-phosphate dehydrogenase (GAPDH), of ponatinib-treated cells relative to vehicle-treated cells.…”
Section: Immunoblot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, ponatinib also manifests inhibitory activity toward PDGFR, KIT, as well as FGFR (21,22). Although it has been reported that ponatinib is active against BaF3 cells stably expressing Y823D KIT in vitro (22) and D816V KIT-positive mast neoplastic cells (10), the in vivo effect remains to be examined.…”
Section: Introductionmentioning
confidence: 99%